El uso de la tecnología en adolescencias de cuerpos grandes y la objetualización en y a través de la práctica nutriológica. Una propuesta de comunicación desde la fenomenología - Herrera Ramírez, Débora (2024)
We tend to see objectification as a negative act in clinical practice, yet Svenaeus makes us reflect that it has in fact allowed for a better understanding of the functioning and composition of the body. In this article, from his epistemological proposal, we will address the good and the bad forms of objectification in the nutritional practice of adolescents with large bodies by using visualization technologies, specifically electrical bioimpedance. Finally, from a hermeneutics and phenomenology standpoint, we propose that in nutritional practice, in addition to treating the biological body, we also treat the lived body of adolescents, based on listening to and understanding their being/existence in the world.